2019
DOI: 10.3389/fphar.2019.00523
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Dichloroacetate Stimulates Angiogenesis by Improving Endothelial Precursor Cell Function in an AKT/GSK-3β/Nrf2 Dependent Pathway in Vascular Dementia Rats

Abstract: Sodium dichloroacetate (DCA) is a mitochondrial pyruvate dehydrogenase kinase inhibitor, and has been shown to display vasoprotective effects in chronic ischemic stroke. The purpose of this study was to evaluate the therapeutic effect of DCA on vascular dementia (VD) and endothelial progenitor cell (EPC)-mediated angiogenesis. After cerebral ischemia-reperfusion in rats, DCA was administered continuously for 21 days; following which, histological analysis, and cognitive functional tests were conducted. Rat bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…Nissl's staining can show cellular necrosis [34] but not apoptosis. The increase in the number of Nissl bodies (chromatin granules) showed the reduction in neuronal necrosis [35]. Nissl staining demonstrated that the number of surviving neurons and Nissl bodies was lacking in the necrosis status of neurons [36].…”
Section: Nissl's Stainingmentioning
confidence: 99%
“…Nissl's staining can show cellular necrosis [34] but not apoptosis. The increase in the number of Nissl bodies (chromatin granules) showed the reduction in neuronal necrosis [35]. Nissl staining demonstrated that the number of surviving neurons and Nissl bodies was lacking in the necrosis status of neurons [36].…”
Section: Nissl's Stainingmentioning
confidence: 99%
“…Increasing evidence has suggested that aberrant angiogenesis may play a role in the development of VaD, but its precise role remains controversial. A significant association between angiogenesis activity and cerebrovascular disease, which is a significant contributor to VaD, has been reported (Callahan et al, 2020), whereas other studies have indicated that promoting angiogenesis, especially in functional blood vessels, can reduce the extent of ischemia and improve cognition in VaD (Yang et al, 2017;Zhao et al, 2019). Clearly, more studies are needed to better understand the potential of angiogenesis as an intervention target.…”
Section: Discussionmentioning
confidence: 99%
“…The major reason may be the ameliorated oxidative injuries, which was verified by results of ROS, MDA, SOD, and GSH in vivo. Although there are a series of pathophysiological changes after cerebral ischemia, oxidative stress is still one of the most serious strikes among Ca 2+ overload, excitatory amino acid overexpression, inflammatory response and so on (Zhao et al, 2019;Luca et al, 2015). During cerebral ischemia, mitochondrial function is abnormal with free radicals accumulation, which leads to lipid, protein, and DNA damage, causing apoptosis and irreversible necrosis.…”
Section: Discussionmentioning
confidence: 99%